Dampak Destinasi Wisata Halal Terhadap Pemanfaatan Potensi Ekonomi Kreatif Bagi Masyarakat Di Gunung Luhur Negeri Di Atas Awan - Deden Hidayat; budiman budiman (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2020)
Determining the potential of the economic sector in regional development is important as an effort to allocate available resources appropriately. The potential growth of the economic sector in an area is believed to encourage the growth and development of other economic sectors in the local area and the economy of the surrounding area. The research uses descriptive qualitative methods to explain existing phenomena with developed economic potential. The results of research and field observations in the economic field of this study produce data on the economic field and the income generated either in the tourism sector or sectors outside of tourism. Like a gold mine of trade outside the country's tourist destinations above the clouds and agriculture. Community income from the tourism sector has a component of 33% and outside the tourism sector has a higher level of 67%. This result is in accordance with the geographical and cultural location of the community in which 90% of their livelihood is farming. For them, income outside of farming is just an addition, not a main source of livelihood. Judging from the income obtained by K1 as much as 13% in the tourism sector and 30% outside the tourism sector. Then K2 in the tourism sector as much as 12% and outside the tourism sector as much as 17%. In K3 8% and 20% in the non-tourism sector. So it can be concluded that the level of utilization of the creative economy sector can be utilized even though it is not maximized.Keywords: Halal Tourism, Economic Potential, Income, Community